Danielâ€™s Use of Å Bá¸¤ and Its Worship Implication - Elisha Marfo (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2023)
Different concepts and motifs have been studied from the book of Daniel by expositors and interpreters without much consideration to the Aramaic terms that have worship nuances, undertones, and connotations. Through a contextual study, this paper contends that the Aramaic ×©××‘×— highlights worship and its implication as integral to the book of Daniel. The study argues that ×©××‘×— is an Aramaic worship expression and its contextual use emphasizes the sovereignty of God. The termâ€™s usage in Daniel highlights the milieu of worship and uplifting either a deity or gods and the God of heaven. However, when idol worship is amplified, the effect is the pronouncement of judgment on the people carrying out such worship.